Therapeutic Effects of Human Urine-Derived Stem Cells in a Rat Model of Cisplatin-Induced Acute Kidney Injury In Vivo and In Vitro - Bishao Sun; Xing Luo; Chengfei Yang; Peilin Liu; Yang Yang; Xingyou Dong; Zhenxing Yang; Jie Xu; Yuanyuan Zhang; Longkun Li (Stem Cells International)
Acute kidney injury (AKI) is an extremely dangerous clinical syndrome with high morbidity and mortality. Stem cell-based therapies have shown great promise for AKI treatment. Urine-derived stem cells (USCs) are a novel cell source in tissue engineering and cell therapy which provide advantages of simple, noninvasive, and low-cost harvest methods, efficient proliferation, and multi-differentiation potential. Here, we described the therapeutic effects of USCs in a rat model of cisplatin-induced AKI as a novel therapy. In vivo, the intravenous administration of USCs alleviated the renal functional damage in AKI rats, for the levels of blood urea nitrogen (BUN) and serum creatinine (SCr) were significantly decreased. The USCs-treated group also exhibited improved histological and ultrastructural changes, promoted proliferation, and inhibited apoptosis in renal tissues. After the USC therapy, the expression levels of proinflammatory cytokines (TNF-α and IL-6) and apoptosis-related proteins (BAX and cleaved caspase-3) were downregulated. In addition, the presence of a few GFP-labeled USCs was confirmed in rat renal tissues. In vitro, rat tubular epithelial (NRK-52E) cells were incubated with cisplatin to induce cell damage and then cocultured with USCs. After coculture with USCs, the cisplatin-induced NRK-52E cells showed higher cell viability and a lower apoptosis ratio than those of the control group, and cell cycle arrest was improved. In conclusion, our results demonstrated that USC therapy significantly improved the renal function and histological damage, inhibited the inflammation and apoptosis processes in the kidney, and promoted tubular epithelial proliferation. Our study exhibited the potential of USCs in the treatment of AKI, representing a new clinical therapeutic strategy.